ANALISIS PELAKSANAAN STRATEGI DISTRIBUSI PUPUK (Studi Evaluasi Penjualan Pupuk Urea Bersubsidi PT. Pupuk Iskandar Muda Perwakilan Riau dan Kepri, Kasus Wilayah Kampar) - Siti Fatimah; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted at marketing representative office of Pupuk Iskandar Muda company in Pekanbaru, Riau. The research problem is how the implementation of distribution at marketing representative office of Pupuk Iskandar Muda company in Riau and Kepri Kasus in Kampar region. This reseach aims to determine the implementation of fertilizer distribution at Pupuk Iskandar Muda company in Kampar region and to identify the obstacles faced in implementing the distribution process.This study was used quantitative descriptive analysis method and using the distribution theory that argued by some experts that uses Warehousing, Transportation, proper type, proper quantity, proper time, proper cost, proper place, proper quality. indicators as a measurement of the implementation distribution strategy Pupuk Iskandar Muda company in Riau and region representatives in Kampar case. This research uses data collection techniques with interviews and questionnaires, sampling technique with census method. Data source is divided into two primary data. Source data is the source of information obtained through questionnaires, interviews with informants and secondary data obtained through the documents available on the Pupuk Iskandar Muda company. The result of this research obtained it could be seen that the distribution strategy implementation Pupuk Iskandar Muda company in Kampar region categorized simply efective.Keywords: warehousing, transportation, proper type, proper quantity, proper time, proper cost, proper place, proper quality.